Evaluación de la calidad del agua en sistemas de recirculación para la producción de chame (Dormitator latifrons) - Macías Silva, Cinthya Mariana (2025)
The research focused on the implementation of a recirculation system for the production of Chame (Dormitator latifrons), composed of 900-liter pools and PVC filters. For six months, physicochemical and microbiological parameters, including dissolved oxygen, pH, temperature, total hardness, chlorides, DBO5, and total coliforms, were monitored, using the Water Quality Index (ICA-Dinuis) to evaluate the suitability of the water. The AQI remained mostly in the "good" range, although it showed a slight decrease in the final months due to the accumulation of nutrients and organic matter. The statistical analysis by ANOVA revealed that there were no significant differences, the physical filters recirculate the nutrients in the same way, however the total coliforms, where T3 proved to be the most effective. Additionally, DBO5 and total phosphorus values reflected organic accumulation, suggesting the need to maintain and clean the filters more frequently. The total costs amounted to 1205.06 USD, evidencing a reasonable budget for an aquaculture system. The design of the system considered local factors and materials such as geomembranes, shading meshes, and pumps. Overall, the recirculation system proved to be a practical solution for Chame cultivation, ensuring stable conditions and controlled operating costs.